CIPPO Model Evaluation on the English Language Training Program At the Indonesian Navy Education Services - Nani Kusmiyati; Hamidah; Kadir (Program Studi S3 Ilmu Manajemen, 2023)
This study describes the implementation of the English Language Education and Training program at the Indonesian Navy Education Service for Indonesian Navy personnel. This study applies a descriptive qualitative method using the CIPPO model (Context, Input, Process, Product and Outcome). To get the data, the researchers conducted interviews, observation, documentation, focus group discussions and questionnaires. From the data obtained through interviews, observation, documentation, focus group discussions and CIPPO model questionnaires using a Likert scale (1 to 5) the context aspect shows 3.81, the training has been carried out based on the objectives, educational plans and activity plans. The input aspect shows 3.59, it supports the training process. The process aspect shows 3.82, the training process can run smoothly. The product aspect shows 3.96, the results of the training are satisfactory. The outcome aspect shows 3.95, the training has a good impact on human resources and institutions in the Navy. This research has the novelty that English Education and Training at DISDIKAL really needs an in-depth evaluation of the implementation of Education and Training. So far, the evaluation is still based on reports on the completion of training